Analisis Perencanaan Biaya Dan Waktu Pada Pekerjaan Konstruksi Pembangunan Jalan Dan Jembatan Bypass Mamminasata Segmen I Dan II - Novry Allo Palita; Muhammad Natsir Abduh; Savitri Prasandi Mulyani (Program Studi Teknik Sipil Universitas Bosowa, 2026)
The aim of the research is to determine the differences in costs and completion times for road and bridge construction projects. The research method used in this study is quantitative research. The difference in normal project work implementation time is 510 working days, after accelerating the work using the time cost trade off method using 2 (two) alternatives, namely additional working hours (overtime) which takes 490 working days, while with the alternative additional labor requires 489 working days. The total cost used before acceleration was Rp. 108,899,888,900 after acceleration using additional working hours became Rp. 100,361,229,776 and saved costs of Rp. 8,538,659,123 and after acceleration with additional workers became Rp. 97,309,953,040 and saved costs of Rp. 11,589,935,859.